Broad emission band in GaN epitaxial layers grown on 6H-SiC and sapphire - Monteiro, T.
Mid-band-gap emissions in GaN epilayers grown on 6H-SiC and sapphire are studied by time-resolved spectroscopy (TRS). The yellow luminescence peaking at ca. 2.2 eV at low-temperature shifts to higher energies with increasing temperature. The presence of emission with the same characteristics in samples grown on different substrates and by different processes indicates that the defects responsible for the emission are of intrinsic nature but dependent on the cubic or hexagonal habit of the crystals. TRS are compared with cathodoluminescence (CL) in a scanning electron microscope (SEM) and optically detected magnetic resonance (ODMR) data.